The Modern Trends of Continuous Technological Education in Ukraine from the Perspective of European Integration - ZHERNOKLIEIEV, Igor (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2015)
The paper examines, on the basis of modern domestic and foreign scientificsources, the state and trends in the sphere of life long education in Ukraine, followedby the prospect of joining the European educational space.